Automated system for monitoring and control of the liquid wax production process - Martín Díaz-Choque; Carlos Dávila-Ignacio; Augusto Sanchez-Ayte; Guillermo Morales-Romero; Almintor Torres-Quiroz; Nestor Alvarado-Bravo; Florcita Aldana-Trejo (Institute of Advanced Engineering and Science, 2021)
This article describes the design of an automated system for the automatic monitoring and control of the liquid wax production process, in order to quantify its effect on productivity indicators. For which initially the procedure for obtaining the automation will be described; then the results obtained will be presented, the same ones that will be identified through a comparative analysis. During the investigation it was determined that, through the use of a programmable logic controller, it was possible to improve the precision of the dosage of components in the liquid wax production process; By achieving acorrect dosage, it is achieved that the physical-chemical factors that intervene in the quality of the final product, which are the pH and specific density, are within the limits established by the company, this is reflected in the decrease 38.77% of the amount of monthly loss of raw material, thus achieving the optimization of the productivity of the production of liquid wax by 83.69% per month, compared to the non-automated process.